Uniformly dispersed and controllable ligand-free silver-nanoparticle-decorated TiO2 nanotube arrays with enhanced photoelectrochemical behaviors - Bian, Haidong (2013)
Homogeneously dispersed silver nanoparticles (AgNPs) were successfully decorated onto the surface of TiO2 nanotube arrays (TNTA) by means of an in situ photoreduction method. TNTA films as supports exhibit excellent properties to prevent agglomeration of AgNPs, and they also avoid using polymer ligands, which is deleterious to enhancing the properties of the fabricated NPs. The silver particle size and its content could be controlled just by changing the immersion time. Detailed SEM and TEM analyses combined with energy-dispersive X-ray spectroscopy analyses with different immersion times (5, 10, 30, 60 min) have revealed the variation tendency. The prepared Ag/TNTA composite films were also characterized by XRD, X-ray photoelectron spectroscopy, and high-resolution TEM. The UV/Vis diffuse reflectance spectra displayed a redshift of the absorption peak with the growth of AgNPs. The photocurrent response and the photoelectrocatalytic degradation of methyl orange (MO) were used to evaluate the photoelectrochemical properties of the fabricated samples. The results showed that the photocurrent response and photoelectrocatalytic activity largely depended on the loaded Ag particle size and content. TNTA films with a diameter of 17.92 nm and silver content of 1.15 at % showed the highest photocurrent response and degradation rate of MO. The enhanced properties could be attributed to the synergistic effect between AgNPs and TiO2. To make good use of this effect, particle size and silver content should be well controlled to develop the electron charge and discharge process during the photoelectrical process. Neither smaller nor larger AgNPs caused decreased photoelectrical properties.